Strain partitioning in highly oblique rift settings: Inferences from the southwestern margin of the Gulf of California (Baja California Sur, México). Issue 12 (21st December 2019) - Bonini, Marco; Cerca, Mariano; Moratti, Giovanna; López‐Martínez, Margarita; Corti, Giacomo; Gracia‐Marroquín, Diego
Abstract: This study aims to analyze the modalities of strain accommodation within a highly oblique rift, taking the Gulf of California as a prototype. Rifting in the Gulf of California is accomplished by intra‐Gulf strike‐slip (transform) faults, and mostly dip‐slip displacement on the rift‐margin faults. We have collected fault‐slip data and samples for radiometric dating at selected sites in southeastern Baja California, which is host to the southwestern margin of the rift. We have identified three styles of faulting, particularly (1) WSW‐dipping normal faults, (2) E‐ENE‐dipping normal faults, and (3) steep NNE‐NE‐trending left‐lateral faults. The E‐ENE‐dipping normal faults define the western margin of the Gulf of California rift and are most likely coeval (late Miocene to recent) with both the NNE‐NE‐trending left‐lateral faults and some of the WSW‐dipping faults. Fault‐slip data have often been collected on potentially active Gulf of California rift‐margin faults, which invariably display dominant dip‐slip kinematics (generally with minor dextral component). Distribution of extension directions determined from stress inversion of brittle fault kinematic data indicates a peak of 080°–090°, which is strikingly similar to the orientations of T axes from earthquake focal mechanisms of both rift‐margin normal/faults and intra‐Gulf strike‐slip faults. These findings suggest that this stretching may have been occurring throughout the protracted rift history. Furthermore, highly oblique rifts do not show across‐rift variations in the orientation of local extension, which is instead typical of continental rifts with lower obliquity. Plain Language Summary: Divergent movement between tectonic plates extends continental crust that progressively thins and subsides generating tectonic depressions called continental rifts. With increasing extension, continental rifts can eventually break through the continental lithosphere and become the locus of creation of new ocean crust. With sufficient tectonic subsidence, a rift can be invaded by ocean water at some point during the rifting process. The displacement vector between the diverging plates may range from orthogonal to oblique, relative to the orientation of the boundary between the plates. The Gulf of California exemplifies a highly oblique continental rift produced by the displacement of Baja California Peninsula with respect to mainland Mexico. Ongoing rifting in the Gulf of California produces intense seismicity, and one long pending question is how deformation is accommodated within highly oblique continental rifts, particularly whether the style of deformation changes from the rift margins toward the rift interior. Analysis of faults exposed along the southwestern rift margin (southeastern Baja California), and its comparison with characteristics of historical seismicity generated by the long strike‐slip faults underwater in the Gulf of California shed new light on the kinematics of high obliquity continental rifts and improves our understanding of the ongoing deformation of our planet. Key Points: Fault‐slip data and samples for radiometric dating have been collected from the southwestern margin of the Gulf of California oblique rift Rifting in southeastern Baja California is controlled by E‐ENE‐dipping normal faults coeval with NNE‐NE‐trending accommodation zones Gulf of California rifting is partitioned into intra‐Gulf strike‐slip and rift margin normal faults that both respond to East‐West extension